Periodontal status of mentally handicapped school children in Caracas, Venezuela. A cross-sectional study. - Mariana Morales-Chávez; Alejandro Rada-Berroteran; Leina Arcila-Ramos (Universidad de Concepción., 2014)
Periodontal disease is a chronic multifactor pathology, characterized by the progressive destruction of the dental structures support tissues. Patients with some type of disability have a higher predisposition to develop periodontal disease, due to bad hygiene, product of their motor and psychological deficiencies, and to their systemic alterations that difficult the defense against periodontopathogenic microorganisms. The purpose of this study was to evaluate and compare the periodontal status of a group of children with special needs, and a control group. 47 patients with mental retardation and Down syndrome from three special education centers, and 31 healthy patients of ages ranging from 6 to 15 years, were dentally evaluated, to determine their plaque index, gingival index, and the presence of calculus. After gathering the data and tabulating the results, a 1.08 plaque index was determined, and a gingival index of 1.03, corresponding to a mild gingivitis in the study group. On the other hand, on the group of regular patients, there was a 1.08 PI and a 0.96 GI. Calculus percentage was similar on both groups. However, a large percentage of children with mild gingival inflammation was observed in the group of special patients (53.19%,) compared to the control group (29%).